2018
DOI: 10.1111/pce.13190
|View full text |Cite
|
Sign up to set email alerts
|

A major natural genetic variation associated with root system architecture and plasticity improves waterlogging tolerance and yield in soybean

Abstract: Natural genetic variations in waterlogging tolerance are controlled by multiple genes mapped as quantitative trait loci (QTLs) in major crops, including soybean (Glycine max L.). In this research, 2 novel QTLs associated with waterlogging tolerance were mapped from an elite/exotic soybean cross. The subsequent research was focused on a major QTL (qWT_Gm03) with the tolerant allele from the exotic parent. This QTL was isolated into near-isogenic backgrounds, and its effects on waterlogging tolerance were valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 74 publications
2
50
1
Order By: Relevance
“…Interestingly, differences in adventitious root formation were also observed between Vietnamese genotypes with contrasting tolerance [167], hinting at an importance of morphological traits, as also seen for cereals (see above). Crosses of the susceptible line S99-2281 and another tolerant line, PI 561271, revealed two more QTLs on chromosomes 3 and 10 [160,168] (see also Table 4). The QTL at chromosome 3 was narrowed down to a region of 23 genes, and research is ongoing to identify the responsible tolerance gene [168].…”
Section: Screening For Waterlogging Tolerance In the Us And Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, differences in adventitious root formation were also observed between Vietnamese genotypes with contrasting tolerance [167], hinting at an importance of morphological traits, as also seen for cereals (see above). Crosses of the susceptible line S99-2281 and another tolerant line, PI 561271, revealed two more QTLs on chromosomes 3 and 10 [160,168] (see also Table 4). The QTL at chromosome 3 was narrowed down to a region of 23 genes, and research is ongoing to identify the responsible tolerance gene [168].…”
Section: Screening For Waterlogging Tolerance In the Us And Asiamentioning
confidence: 99%
“…Crosses of the susceptible line S99-2281 and another tolerant line, PI 561271, revealed two more QTLs on chromosomes 3 and 10 [160,168] (see also Table 4). The QTL at chromosome 3 was narrowed down to a region of 23 genes, and research is ongoing to identify the responsible tolerance gene [168].…”
Section: Screening For Waterlogging Tolerance In the Us And Asiamentioning
confidence: 99%
“…Notably, seven QTLs were mapped for hypoxia-tolerant index of root development traits [ 145 ]. Furthermore, a tolerant allele of qWT_Gm03 promoted soybean growth under waterlogging stress through regulation of root architecture and plasticity [ 146 ]. Chromosome region analysis showed that these QTLs for flooding tolerance were mainly located on chromosomes 4, 9, 10, 12, 13, and 14 [ 144 , 145 , 146 ].…”
Section: Interaction Of Molecular Mapping and Plant Omics To Floodmentioning
confidence: 99%
“…Furthermore, a tolerant allele of qWT_Gm03 promoted soybean growth under waterlogging stress through regulation of root architecture and plasticity [ 146 ]. Chromosome region analysis showed that these QTLs for flooding tolerance were mainly located on chromosomes 4, 9, 10, 12, 13, and 14 [ 144 , 145 , 146 ]. In addition, proteomic studies indicated that chromosomes 5, 10, 11, and 13 contained abundant flooding response genes [ 20 , 23 ]; however, chromosome 17 contained more tolerant genes [ 23 ].…”
Section: Interaction Of Molecular Mapping and Plant Omics To Floodmentioning
confidence: 99%
“…Previous studies have implicated that when the oxygen supply is difficult to maintain, plants initiate organogenesis with adventitious roots emerging from stem nodes, thus improving gas diffusivity around the root [ 14 , 15 ]. In various plants species, the significance of ROS or hormonal regulation in adventitious roots has been reported extensively [ 15 , 16 , 17 , 18 ], and adventitious root formation has been successfully applied to be the root system architecture in genetic resource development or identification [ 19 , 20 , 21 , 22 , 23 ]. However, the process is largely unknown in rapeseed.…”
Section: Introductionmentioning
confidence: 99%